2008
DOI: 10.1007/s12033-008-9056-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Antioxidants and Human Aging: A Study on Healthy Elderly Tunisian Population

Abstract: The aging has been described by several theories. It was proposed that free radicals are the major factor involved in this process. This gave birth to the free radical theory of aging. This current theory provides the most popular explanation for how aging occurs at the biochemical/molecular level. Ever since 1956, this theory has received widespread attention and a large body of evidence has been accumulated in support of its hypotheses which were subsequently refined. The free radical theory of aging postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is still an open question as to whether increased oxidative stress during aging is mainly caused by enhanced ROS production or decreased ROS scavenger activities, or both (Rao et al 1990; Liu & Mori 1993; Sohal et al 1994; Hussain et al 1995; Sandhu & Kaur 2002; Chehab et al 2008; Sasaki et al 2008). We found that although major ROS scavenger enzyme expression is increased in our Immp2l mutant mice, cellular oxidative stress is still elevated, supporting the notion that increased oxidative stress during aging is mainly caused by enhanced ROS production rather than decreased ROS scavenger activities (Sasaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still an open question as to whether increased oxidative stress during aging is mainly caused by enhanced ROS production or decreased ROS scavenger activities, or both (Rao et al 1990; Liu & Mori 1993; Sohal et al 1994; Hussain et al 1995; Sandhu & Kaur 2002; Chehab et al 2008; Sasaki et al 2008). We found that although major ROS scavenger enzyme expression is increased in our Immp2l mutant mice, cellular oxidative stress is still elevated, supporting the notion that increased oxidative stress during aging is mainly caused by enhanced ROS production rather than decreased ROS scavenger activities (Sasaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The role of these major antioxidant enzymes in aging is currently controversial. Some studies have reported a decrease in the expression or activities of these enzymes during aging (Rao et al, 1990;Sandhu & Kaur, 2002;Chehab et al, 2008). Others have found that expression levels were either unchanged or even slightly increased during aging (Liu & Mori, 1993;Sohal et al, 1994;Hussain et al, 1995;Sasaki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%